(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2011)
Here we describe 41 brachiopod species belonging to the orders Productida, Orthotetida, Orthida, Rhynchonellida, Athyridida, Spiriferida, Spiriferinida, and Terebratulida coming from the Guadalupian lower-middle part of the Pamuçak Formation at Çürük Dað, Antalya (Western Taurus, Turkey). Associated conodonts are also reported and illustrated. The brachiopod taxa are either pedicle attached genera, with one genus also stabilized by penetration of its elongate umbo, or free living concavo-convex semi-infaunal genera; this indicates that the energy of the environment was never very high, as in settings just below the fair weather wave-base or in a back-reef, more protected inner platform. The brachiopods from the Pamuçak Formation are very similar to the Wordian fauna of southeastern Oman, and they are similar to the Guadalupian assemblages of Chios, North Iran, South Thailand, and Salt Range. In comparison they share only a few taxa with the Guadalupian faunas of Central Afghanistan and Karakorum. Therefore the biotic affinity of the Guadalupian brachiopods of the Pamuçak Formation is clearly peri-Gondwanan. The brachiopod record at Çürük Dað has implications for understanding the pattern of the end-Guadalupian (pre-Lopingian) biotic crisis. The pre-Lopingian crisis assemblages are quite diverse and nearly totally consist of Guadalupian genera and species except for a single Lopingian incomer. Their stratigraphic range terminates rather abruptly and the following 120 metres of shallow water limestones are barren of brachiopods, after which there is the first occurrence of Lopingian brachiopod taxa, which show a much lower biodiversity. This pattern is different from that observed in South China and it shows that the end-Guadalupian crisis is not only characterized by taxonomic selectivity, but also by a strong local control on the extinction/recovery pattern of some groups.